Dukuh Siladri Kisah Seorang Pertapa Pada Cerita Rakyat Bali - Luh Putu Sri Ariyani; Tuty Mariyati; Nengah Bawa Atmadja (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This study examines the oral tradition of Dukuh Siladri, the Story of a Hermit in Balinese Folklore. The aim is to understand the ethnoecology of the story using content analysis combined with deconstruction tied to radical hermeneutics. The results of the study indicate that the ethnoecology or ethno-Palemahan in the story begins with the idea that nature recognizes three states: heaven (above), hell (below), and a mixed realm between heaven and hell (middle). Humans and other living creatures exist in a mixed realm, thus bound to heaven and hell. The ideal human aspiration is to realize heaven and avoid hell, by obeying religion at the level of thought, speech, and action. This pattern is applied to the relationship between humans and God/gods, guided by ethno-Parhyangan. Another application is to social structures, referring to ethno-Pawongan. In social structures, there are always humans who obey the principles of virtue or vice versa. Humans must side with virtue and at a certain point follow the wanaprastha way of life, namely becoming a hermit in the forest in preparation for realizing heaven in the upper world. The application of religion to human relations with the natural environment is very important. For example, forests consisting of flora and fauna must be treated as friends based on compassion, because they can help humans in times of joy and sorrow. The purity and preservation of the natural environment must be maintained through bhuta yajnya.